Translation Shift Analysis Of Verb And Verb Phrase In Subtitling Of The Hunger Games Movie - Mina, Muh. Ikmal, Dra. Dwi Haryanti, M.Hum, Siti Fatimah, S.Pd.,M.Hum (2013)
This research studies the verb and verb phrase in subtitling of The Hunger Games movie. The objectives of study are to identify the translation shift and to describe the equivalence of verb and verb phrase found in The Hunger Games movie and its subtitling. This research is a descriptive qualitative research. The data are text containing sentences found in the data source which is the translation shifts, especially verb and verb phrase. The data sources are English subtitling of The Hunger Games movie and Indonesian subtitling of The Hunger Games movie. The data are analyzed by using comparing method. The result of the study shows that, there are two translation shifts of verb and verb phrase, namely; category shifts and level shifts. From 228 data, there found the category shift, those are 7 or 3.07 % data from 228 data of verb into adjective, 1 or 0.44 % datum from 228 data of verb into adverb, 6 or 2.63 % data from 228 data of verb into noun, 44 or 19.29 % data from 228 data of verb is not translated, and 1 or 0.44 % datum from 228 data of verb is translated into preposition. Besides, the level shift is 15 or 6.58% data from 228 data of verb into verb phrase. Also, the writer finds two types of translation shift of verb phrase; category shift and level shift. The category shift is 16 or 7.02% data from 228 data of verb phrase is not translated. While the level shifts, those are 11 or 4.82 % data from 228 data of verb phrase into adjective, 4 or 1.75 % data from 228 data of verb phrase into adverb, 8 or 3.51 % data from 228 data of verb phrase into noun and 115 or 50.44 % data from 228 data of verb phrase is translated into verb. Secondly, the equivalence of translation divided into equivalent translation and non equivalent translation. The equivalent translation is 161 or 70.61% data and non equivalent translation is 67 or 29.39% data from 228 data. From these percentages, it can be concluded that the translation shifts of verb and verb phrase in subtitling of The Hunger Games Movie is an equivalent translation.